Phytochemical analysis, stability, and antimicrobial activity of eighteen medicinal plants studied against five multi-drug resistant human pathogens - Malya, G. Dharshana; Bhattacharjee, Jhumpa; Mukherjee, Sahana; Deka, Shubhajyoti; Saikia, Lahari; Nandi, Shoma Paul (European Journal of Clinical and Experimental Medicine, 2024)
<p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Introduction and aim. Several medicinal plants from India have been reported to be effective against human pathogens, but comprehensive comparative studies are scarce. The aim of this study has been to evaluate and compare the antimicrobial activity, phytochemical composition, and stability at different temperatures and pH of ethanolic extracts of eighteen Indian medicinal plants which are prevalent in North-east India and thrive abundantly. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Material and methods. These plants included Syzygium cumini, Cannabis sativa, Camellia sinensis, Murraya koenigii, Alstonia scholaris, Terminalia chebula, Flemingia strobilifera, Azadirachta indica, Prunus persica, Euphorbia thymifolia, Averrhoa carambola, Paderia foetida, Psidium guajava, Spondias pinnata, Garcinia cowa, Litsea cubeba, Micania macrantha, and Phlogocanthus thyrsiflorus. Their potent medicinal properties made them the ideal choice for this study which included the use of agar well diffusion method and phytochemical analysis. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Results. Agar well diffusion has been used to test their antibacterial activity, which demonstrated higher antibacterial activity of G. cowa extract against Vibrio cholerae and Staphylococcus aureus, whereas S. pinnata extract was most effective against V. cholerae and Enterococcus faecium. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Conclusion. Phytochemical analysis revealed the presence of tannins, alkaloids, saponins, glycosides, steroids, terpenoids, flavonoids, and phenols. The antimicrobial activity of these plant extracts remained stable at higher temperatures and varying pH levels.